Effect of bispectral index-guided total intravenous anesthesia in younger children: A prospective, randomized, controlled trial - Liu, Guoliang; Zhang, Jianmin; Wang, Fang; Li, Lijing; Zhang, Xuemei (Frontiers in Neurology, 2022)
Background: BIS-guided total intravenous anesthesia (TIVA) is widely used in children, but few studies have attempted to evaluation of the effect of BIS-guided TIVA in younger children. This study aimed to evaluate the effect of bispectral index (BIS) guidance during TIVA in younger children during anesthesia. Methods: This study is a prospective, randomized, single-blind and controlled clinical trial. This study enrolled pediatric patients (aged 1-3 years) who were scheduled for surgery under TIVA with propofol and remifentanil. The children were randomly assigned to the BIS group (group B) and standard clinical practice group (group S). The BIS values in group B were maintained at 45–60. The anesthesiologist controlled the depth of anesthesia in group S according to the variation in the clinical signs of the children. The time of extubation, duration of stay in post-anesthesia care unit (PACU), as well as BIS values, heart rate (HR), mean arterial pressure (MAP), pulse oxygen saturation at eight time points, propofol consumption, and postoperative adverse reactions were recorded. Results: There was no significant difference in time to extubation 15(10,21) vs 14 (11,20) and duration of stay in PACU 27 (20,37) vs 29 (22,39) between the group B and group S. BIS values and MAP significantly differed among the eight time points as well as between the two groups (P < 0.05). At the time points T5, T6 and T7, the BIS values in group S were significantly higher than those in group B (P<0.05). MAP in group B was lower than in group S at T5, T6, T7, and T8. The total amount of propofol administered in group B was higher than in group S. Conclusions: The use of BIS-guided total intravenous anesthesia in younger children does not shorten the time of extubation and the duration of stay in the PACU，while can maintain the proper depth of anesthesia than standard clinical practice group.